2007
DOI: 10.1093/bioinformatics/btm513
|View full text |Cite
|
Sign up to set email alerts
|

Low folding propensity and high translation efficiency distinguishin vivosubstrates of GroEL from otherEscherichia coliproteins

Abstract: Motivation: Theoretical considerations have indicated that the amount of chaperonin GroEL in Escherichia coli cells is sufficient to fold only $2-5% of newly synthesized proteins under normal physiological conditions, thereby suggesting that only a subset of E.coli proteins fold in vivo in a GroEL-dependent manner. Recently, members of this subset were identified in two independent studies that resulted in two partially overlapping lists of GroEL-interacting proteins. The objective of the work described here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…These observations are also consistent with the results of Tartaglia et al. [15] and those of another study that showed that GroEL substrates have lower folding propensities compared with GroEL‐independent proteins [21]. Folding propensity was determined in the Noivirt‐Brik et al.…”
Section: Relationship Between Groe Dependence and Solubilitysupporting
confidence: 91%
See 1 more Smart Citation
“…These observations are also consistent with the results of Tartaglia et al. [15] and those of another study that showed that GroEL substrates have lower folding propensities compared with GroEL‐independent proteins [21]. Folding propensity was determined in the Noivirt‐Brik et al.…”
Section: Relationship Between Groe Dependence and Solubilitysupporting
confidence: 91%
“…Fischer’s exact test was used to test whether the overlaps are statistically significant. The P ‐value for an overlap of 80 proteins (an overlap of 136 has been reported previously [21] when homologs were included) between classes I, II and III [12] when combined and the set identified by Chapman et al. [14] is < 10 −33 .…”
Section: Experimental Identification Of Proteins That Interact With Gmentioning
confidence: 76%
“…Our results (Figs. 1 and 2), together with complementary recent studies, 39,40 provide evidence that such a link indeed exists. We have exploited the relationships between these quantities (arrows A, B and C in Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Perhaps the best-characterized molecular chaperone is the prokaryotic chaperonin GroEL, which, together with its cochaperonin cohort GroES, facilitates the folding of many proteins. [1][2][3][4][5][6] The roles played by such chaperones are even more crucial when the cell experiences stress, when even those proteins that can otherwise fold by themselves fold with decreased efficiency. [7][8][9] The primary role played by GroEL appears to be to associate reversibly with folding intermediates that would otherwise associate irreversibly with each other through exposed hydrophobic surfaces and, thereby, aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…6,[12][13][14][15] In fact, GroEL appears to have evolved to become a universal chaperone that can bind to different nonnative conformations of many different proteins, irrespective of their native structures. 12,[16][17][18] It can bind to many of the intermediates that accumulate on the folding pathways of proteins, including unfolded forms, early unstructured intermediates, molten globule intermediates, late structured intermediates, and native-like states.…”
Section: Introductionmentioning
confidence: 99%